The Influence of Leadership Competencies on Sustainable Funding of Local Non-Governmental Organizations in Uganda - Kyalimpa, Paul; Asiimwe, John Baptist; Netswera, Fulufhelo Godfrey; Rankhumise, Edward Malatse (ournal of Public Administration and Governance, 2017)
Introduction: When a leader with a vision launches a Local Non-Governmental Organization (LNGO or NGO), the NGO’s motivation and decision-making often become intertwined with the leader’s personality and character to the effect that it may collapse when the NGO leader departs. Uganda has a higher percentage of NGOs inactivity and mortality due to unsustainable funding. Therefore, this study investigated the influence of NGO leadership competencies on sustainable funding of NGOs. Methods: This study utilized a descriptive correlation design. A proportionate stratified sample of 103 NGOs was obtained and their leaders were interviewed using self-administered questionnaires. Records reviews were conducted to obtain data on NGO funding. Results: This study found a 90.1% to 100% agreement by participants on possession of the various leadership competencies by the NGO leaders. A marked rise in incomes from all sources was recorded between 2010 and 2014, with external donors, local donors, and own income accounting for 67%, 13.5%, and 19.5% of the total funds, respectively. The average donor-dependency ratio and survival ratio over the 5-year period was 80.54% and 71.216 days respectively. The NGO leader/CEO understanding and working with whatever resources that are available (β=-9.802, P=.002) and spearheading the implementation of major investment decisions (β=15.720, P=.004) were the only competencies found to be statistically significant predictors of NGO financial sustainability. Recommendations: Government funding of NGOs, prioritization of Income Generating Activities and capacity building of NGO leaders in effective and efficient resource utilization and investment by NGOs, are key to NGO Survival.
Keywords: Leadership Competencies; Sustainable Funding; Local NGOs